A population-based study of Swedish gynecologists' experiences of working in abortion care - Hammarstedt, Meta; Lalos, Ann; Wulff, Marianne (Acta obstetricia et gynecologica Scandinavica, 2006)
Background. Legal abortion is a recurrent part of gynecologists' work. The aim of the study was to describe Swedish gynecologists' clinical and emotional experiences when working in abortion care. Further aims were to elucidate their perception of women's motives for having an abortion as well as looking for possible demographic and gender differences. Methods. A questionnaire comprising both structured and semi-structured questions was sent to a random sample of 269 Swedish gynecologists. The response rate was 85%. Results. The female gynecologists were younger (27-59 years) and more numerous than the males (33-66 years). Almost all believed that gynecologists should be involved in abortion care, and half were opposed to the privilege of refusing to work with termination of pregnancy. The gynecologists supported the shift from surgical to medical abortions but not to their being managed in primary healthcare. A few gynecologists (n=42) had considered changing their job because of termination of pregnancy being part of their work. Misgivings occurred sometimes in connection with surgical and late abortions (n=60 and n=108 respectively). Few gynecologists (n=33) had felt inadequate when encountering abortion patients and more than half thought that working with termination of pregnancy was a positive experience. The gynecologists believed that continuing professional development and ongoing guidance of termination of pregnancy matters were important. Conclusions. In general, Swedish gynecologists have no doubts about taking part in and performing termination of pregnancy. Their clinical and emotional experience, as expressed in this study, as well as their perception of women's motives for abortions, indicate that they have gained deep insights and developed their professionalism in their work with termination of pregnancy.